Multigravid Women with Uterine Rupture: A Case Report - Firmansyah Basir; Adnan Abadi; Abarham Martadiansyah; Cindy Kesty; Febi Stevi Aryani; Murwani Emasrissa Latifah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Introduction: Uterine rupture is the discontinuation of the uterine scar that creates connection between uterine and peritoneal cavity. The most common etiology for uterine rupture is dehiscence of uterine scar tissue from previous cesarean section. In patient with uterine rupture and fetal expulsion to the peritoneal cavity, fetal survival becomes extremely poor. Therefore, it is important for clinician to understand the uterine rupture and be able to give prompt treatment in order to prevent maternal and fetal morbidity and mortality. Case Presentation: A 34-year-old woman, G3P2A0 38 weeks of gestation complained that she had abdominal pain, couldn’t feel her baby movement, watery discharge since 10 hours before admission. Bloody discharge and trauma were all denied. Patient underwent twice cesarean section before. Patient only had four times antenatal care with obstetrician at 24, 28, 32, and 36 weeks of gestation. She was scheduled for caesarean section at 38 weeks of gestation. Patient looked alert with low blood pressure and tachycardia. On physical examination, we found that she was pale, fundal height could not be determined, and there was no fetal heart rate detected. Speculum examination showed livide portio, closed external orifice of uterus, and inactive blood. There was positive slinger sign and Douglas cavity was bulging. Ultrasound examination showed intrauterine fetal demise, complete uterine rupture on lower segment, and positive sign of free fluid on abdominal cavity. Patient underwent operation and we found the died male neonate was in the peritoneal cavity and the placenta was still attached in the uterine cavity. We delivered the baby and placenta completely. There was uterine rupture on the previous CS scar, the edge of the uterine wound was regular with no necrosis and extended to the right side of uterus. Then, we performed hysterorrhaphy in order to stop the bleeding and repair the uterus, and we also performed tubal ligation. The died neonate had maceration grade I. Conclusion: Uterine rupture causes poor fetal and maternal prognosis. Early diagnosis and prompt treatment is really important in uterine rupture. Prevention of uterine rupture could be done by meticulous antenatal care, especially visiting to obstetrician in order to review maternal and fetal condition and determine mode of delivery.